PENGUKURAN KINERJA PRODUKSI HOT STRIP MILL DENGAN METODE OVERALL EQUIPMENT EFFECTIVENESS (OEE) (Studi Kasus pada Industri Baja di Cilegon, Banten) - Nashrullah Setiawan; Mauvina Annisa (Teknoin, 2017)
The Overall Equipment Effectiveness (OEE) is the performance measurement tool for stabilizing process in industrial manufacturing. It becomes a comprehensive analysis method from a strategic to operational point of view to optimize measurement result.This study aims to examine gap case studies of performance measurement results of Hot Strip Mill production using OEE method in one of the largest steel industry in Cilegon Banten. The research methodology includes determination of measurement variables, secondary data collection (i.e. production time data, total production and total product defect), interviews and field observations, and analysis of factors causing the gap between target and actual performance. Based on data processing, the result of performance measurement is: 61% (availability), 63% (performance), 95% (quality) and 42% (OEE). Based on pareto analysis and fishbone diagram, it is known that dominant cause factor is delay time and high demand variation.